If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(4x + -14) + 3(3x + 4) = 0 Reorder the terms: -1(-14 + 4x) + 3(3x + 4) = 0 (-14 * -1 + 4x * -1) + 3(3x + 4) = 0 (14 + -4x) + 3(3x + 4) = 0 Reorder the terms: 14 + -4x + 3(4 + 3x) = 0 14 + -4x + (4 * 3 + 3x * 3) = 0 14 + -4x + (12 + 9x) = 0 Reorder the terms: 14 + 12 + -4x + 9x = 0 Combine like terms: 14 + 12 = 26 26 + -4x + 9x = 0 Combine like terms: -4x + 9x = 5x 26 + 5x = 0 Solving 26 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + 5x = 0 + -26 Combine like terms: 26 + -26 = 0 0 + 5x = 0 + -26 5x = 0 + -26 Combine like terms: 0 + -26 = -26 5x = -26 Divide each side by '5'. x = -5.2 Simplifying x = -5.2
| 3x-54=2x-9 | | r+15=-41 | | 48-12-24=131 | | w+(-12)=-41 | | .05x+x=32.14 | | -43+6x=-103 | | -3(2x-y)=-3(-1) | | 60+8f=-180 | | 5+(-8)-2= | | nn=81 | | 36p=36 | | x/2-9=-23 | | 8n+3-4n-n+11=14 | | 2x+34x=-60 | | 2(3x+y)=2(-9) | | -5b-7=38 | | -4a-2a+5+-9=44 | | 3(2x+3)=48 | | 5.8(x-1)=-0.2x+42.2 | | 125=x-9 | | 5x+40=15 | | -144x^2+100=0 | | 9(x+2)+2(x+2)=6x-6 | | 46-3n=-27 | | 3(2x-4)-2(5x-1)= | | 2x^5(x-x^2+6x^3)= | | 38-10n=-3(n-8) | | 2x^5(x-t^2+6t^3)= | | -4a+5+2a-9=44 | | 13x-15=x-5 | | f(x)=8x^3-2x^2-15x | | 13m+2=4m+110 |